Determination of legal facts and their essential characteristics - Шапенко, Людмила Олександрівна; Костяна, Ірина Юріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The authors of the article found the connection between legal facts and legal consequences for subjects of law based on studying the social mechanism of the origin of the factual situations that found their consolidation in the legal area. By the analysis of the content of the phenomenon being investigated it was determined social, material and juridical component that allows to complete characterizing of legal facts’ role in the legal regulation. Each legal fact has a certain social mechanism of occurrence, which encompasses a set of regularities, preconditions, which cause the appearance of this fact. Study of the structure of this mechanism (its main parts) allows us to distinguish three levels of preconditions:- general social preconditions, which always lie at the basis of the formation of factual circumstances that will be of legal significance;- the special preconditions which are necessary for the emergence of legal facts may exist in a more narrow sphere of social relations, which directly leads to the emergence of a certain category of legal facts;- causes of a single nature, which depend on the will and interests of citizens, officials, organizations. Equally important question to ensure effective legal regulation is the determination of the circumstances that should be legal facts. From the point of view of its social content, the legal fact, first of all, must adequately reflect the social situation, which is regulated by the legal norm. The second requirement for legal facts is their legal reliability. This property reflects, on the one hand, the constant connection of the fact with the social situation, and on the other–the stability of its social content. Legal facts must also have adaptability, the ability to "adapt" to the transformed conditions of the social environment. At first glance, this principle is contrary to the requirements of reliability; however, it is the ability of the actual system of law to regulate social relations and resolve conflicts, flexibly adapting and evolving without sharp turns, which proves the existence of the regulatory potential of legal facts. Legal facts are end owed with social content. However, they represent not only social circumstances; their essence cannot be limited only to the existence of social ties. It should be remembered that legal facts have also legal (normative) content, as it’s an element of the legal form of social relations, one of the means of legal regulation. Along with social and normative constituents there is also a material component, the essence of which is that legal facts are the phenomena of objective reality, since the environment of their origin is the very life and all of them, first of all, are circumstances. That is, legal facts, on the one hand, are concrete circumstances of social reality, which serve as the basis for the emergence of legal consequences, and on the other–this is a legal model, which is enshrined in the hypothesis of the legal norm (or several norms). The results of the study indicate that legal facts are phenomena of both social and legal reality. After all, arising in the material world and spreading its effect on all social relations enshrined in the hypothesis of the legal norms.